Wireless Tire Condition Monitoring System - M SALLEH AMRAN, NUR AIN (IRC, 2020)
Tire pressure monitoring system (TPMS) is an automated system embedded in vehicles’ pneumatic tires. This system monitors each tire’s pressure and temperature. However, the main function of every TPMS available in the market is limited to monitoring these two parameters only. Hence, this research is carried out to propose a development of an improvised Wireless Tire Condition Monitoring System (TCMS) that monitor tire pressure, temperature and predict the lifespan of each tire of a vehicle based on tread thickness. The proposed Wireless TCMS is made up of a temperature and pressure sensor, an ultrasonic sensor, embedded controller or also known as microcontroller unit (MCU) with Wi-Fi module, and batteries. In this proposed Wireless TCMS, the tire tread depth, temperature and pressure data can be optionally shared to the other third parties. As for tire lifespan prediction, mathematical approach will be used by measuring the changes of tread thickness. Presuming that there are abnormalities with the temperature and pressure of a tire, the expected result of this project will be a generation of alert message and a list of nearby workshops or gas stations to the user. Also, a reminder message of tire replacement will be sent when the predicted tire lifespan is reaching an unsafe level. As for conclusion, this project is expected to be able to predict the tire lifespan or tire tread wear and generate immediate notifications when there are abnormalities in the tire.